2021
DOI: 10.2478/hukin-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

Force-Velocity Profile of Competitive Kayakers: Evaluation of a Novel Single Kayak Stroke Test

Abstract: The assessment of the force-velocity (F-V) profile in athletes may have important applications for training prescription, injury management, and fatigue monitoring. This study aimed to assess whether a novel single kayak stroke test (SKST) is able to provide the F-V relationship variables (maximum force, maximum velocity and maximum power) of competitive kayakers with acceptable reliability and external validity. Six female (age: 20.3 ± 3.7 years) and eight male (age: 20.8 ± 2.4 years) elite kayakers performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Conversely, only the PBP maximum power is significantly correlated with the maximum kayak velocity performance (r = 0.80; p < 0.01) (Figure 1) and the related stroke frequency (r = 0.61; p < 0.05) (Table 2). Probably, the differences found between this study and the previous ones (Lum and Aziz, 2020;Petrović et al, 2021) could be due to the different dry-land test protocols performed (dynamic Vs. isometric) and kayak test performance (50 m sprint flatwater kayak Vs. kayak ergometer). On the contrary, the data obtained from the BP exercise show a poor correlation (Figure 2; Table 2) not only between 1RM but also with the P max and the kinematic parameters of the KST analyzed, showing the scant specificity with the biomechanical parameters and the muscular kinetic chains involved during the paddle stroke.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Conversely, only the PBP maximum power is significantly correlated with the maximum kayak velocity performance (r = 0.80; p < 0.01) (Figure 1) and the related stroke frequency (r = 0.61; p < 0.05) (Table 2). Probably, the differences found between this study and the previous ones (Lum and Aziz, 2020;Petrović et al, 2021) could be due to the different dry-land test protocols performed (dynamic Vs. isometric) and kayak test performance (50 m sprint flatwater kayak Vs. kayak ergometer). On the contrary, the data obtained from the BP exercise show a poor correlation (Figure 2; Table 2) not only between 1RM but also with the P max and the kinematic parameters of the KST analyzed, showing the scant specificity with the biomechanical parameters and the muscular kinetic chains involved during the paddle stroke.…”
Section: Discussioncontrasting
confidence: 73%
“…Several studies have verified a positive correlation between strength profile and kayak performance, using isometric strength tests performed in BP and PBP and kayak ergometer performance (Lum and Aziz, 2020;Petrović et al, 2021). Nevertheless, these studies have not considered other relevant dynamic and kinematic parameters involved in both bench lift exercises and flatwater kayak performances; in contrast to the studies mentioned above, our findings have shown a poor correlation, for each bench lift exercise, between the maximum dynamic strength (1RM) and the maximum kayak velocity (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…The sample consisted of 21 male kayakers: 7 sprint specialists and 14 long-distance specialists (age = 21.4 ± 3.14 years [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]; body height = 180.78 ± 6.26 cm; and body mass [BM] = 80.08 ± 7.11 kg). All participants were active competitors at either national ( n = 12) or international level ( n = 9, e.g., Serbian national team), with a minimum competing history of 5 years and a training frequency of a minimum of four times per week (4–12).…”
Section: Methodsmentioning
confidence: 99%
“…This is partially due to difficulty in assessing isolated stroke performance. For this reason, Petrović et al [ 17 , 18 ] recently developed a kayak stroke test sensitive enough to detect differences between competitors in different disciplines. This test is conducted on a custom-made railing system, which, after a kayaker performs the kayak stroke, rolls forward until the rolling stops.…”
Section: Introductionmentioning
confidence: 99%
“…Sprint kayaking success is determined by average velocity over a given distance and has been investigated from a variety of approaches ( Li, 2017 ). Predominantly, biomechanical assessment has been conducted using kinematics ( Baker et al, 1999 ; Kendal and Sanders, 1992 ; Lopez Lopez and Ribas Serna, 2011 ; Sanders and Kendal, 1992 ) and kinetics ( Aitken and Neal, 1992 ; Gomes et al, 2015 ; Mononen et al, 1995 ; Mononen and Viitasalo, 1995 ; Petrovic et al, 2021 ; OnariciGüngöret al, 2023), with attention of the research centring on the upper limbs and the paddle. Focus upon force production and the motion of the paddle, resulting from occlusion of the lower limbs by the kayak shell and the significant association between the magnitude of paddle force and average velocity ( Mononen et al, 1995 ; Mononen and Viitasalo, 1995 ),means the contribution of the legs and the trunk is less well understood.…”
Section: Introductionmentioning
confidence: 99%